The third sector of R&D: literature review, basic analysis, and research agenda. (2nd January 2017) - Hallonsten, Olof
Abstract: The third sector of national innovation systems comprises non-academic, publicly owned R&D organizations that complement universities and private-sector firms and are normally called 'research institutes'. Scholarly attention to these organizations has been scarce, partly a consequence of the theoretical imbalance in favor of conceptualizations of innovation processes as requiring mainly universities, private-sector firms, and governmental authorities to occur and succeed. Similarly, while this third sector often makes up a significant share of national innovation systems, it receives less attention in national research and innovation policy than do, say, universities. This paper argues that the role(s) and function(s) of third sector research institutes deserve to be mapped and analyzed in greater detail in order to understand how various organizational actors interact to produce innovation. From a comprehensive literature review and basic analysis of three institute groups in three Nordic countries, the paper makes a first preliminary analysis of the topic. While this analysis yields some interesting conclusions, its main function is to point the way for future studies. In these, other actors in the system should be investigated in thorough empirical studies, armed with tools from classic sociological systems theory that enhance the conceptual strength of the innovation systems framework and enable the acknowledgement of the role(s) and function(s) of several important organizational actors, not least research institutes.